A thermosetting resin composition and insulating adhesive film thereof
By using modified spherical silicon micropowder in insulating materials and controlling the particle size and distribution variation coefficient, the problems of high melt viscosity and poor dielectric properties of insulating materials in fine circuit fabrication are solved, achieving low melt viscosity, low dielectric loss and high chemical copper bonding strength, making it suitable for FC-BGA insulating films.
Patent Information
- Application Number
- CN202211734990.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-30
AI Technical Summary
Existing insulating materials suffer from problems such as high melt viscosity, weak filling capacity, and affected dielectric properties when used to fabricate fine circuits. In particular, it is difficult to achieve low melt viscosity, low dielectric loss, and high chemical copper bonding strength in high-filling systems.
Modified spherical silica powder was used, with its D50 particle size controlled within the range of 0.1 to 2.0 μm, and the particle size distribution variation coefficient was adjusted to ≥35%. By using amino-modified spherical silica powder in the epoxy system, combined with appropriate surface treatment agents, the bonding force and flowability between the filler and the resin were improved, and the dielectric loss was reduced.
It achieves low melt viscosity, low dielectric loss and high chemical copper bonding strength, making it suitable for fine line filling and solving the application problem of high-filler system insulating materials in FC-BGA.
Smart Images

Figure BDA0004032353470000111 
Figure BDA0004032353470000112 
Figure BDA0004032353470000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulating materials and relates to a thermosetting resin composition and an insulating adhesive film thereof. Background Art
[0002] With the development of printed circuit technology, the additive process has been favored by substrate manufacturers for its ability to achieve extremely low line width / line spacing, which puts forward several requirements for insulating materials: 1. Since the insulating film material needs to be layered on the surface after a layer of circuit is made, it is required that the insulating film material has excellent rheological properties to fill the circuit, so the insulating film needs to have a low melt viscosity; 2. Since the circuit is very thin, sufficient bonding between the circuit and the film is required, and the film needs to have the basic characteristics of the additive process to obtain a higher copper wire bonding force; 3. Since it is necessary to make fine circuits, the roughness of the film after roughening should not be too large, otherwise it will cause the electroplated copper to penetrate too deeply into the insulating film, resulting in interlayer insulation failure. Adding fillers to the film can obtain a lower thermal expansion coefficient. During the preparation process, the filler manufacturer will use physical high temperature to remove the moisture on the surface of the filler. However, even after high temperature heating at 300°C, it is difficult to completely remove the trace bound water remaining on the surface of the filler, and the presence of this trace bound water will affect the dielectric properties of the low dielectric loss film.
[0003] Therefore, in the art, it is desired to find an insulating material that can solve the above problems. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a thermosetting resin composition and an insulating adhesive film thereof.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In one aspect, the present invention provides a thermosetting resin composition, comprising the following components in parts by weight:
[0007] 30-70 parts of epoxy resin (A), 5-500 parts of modified spherical silica powder (B) and 30-70 parts of curing agent (C), wherein the spherical silica powder includes amino-modified spherical silica powder, the D50 particle size of the modified spherical silica powder is 0.1-2.0 μm, and the coefficient of variation of particle size distribution is ≥35%.
[0008] In the present invention, by using modified spherical silica powder in an epoxy system and controlling the range of its D50 particle size and the coefficient of variation of particle size distribution, the resin composition can be used for an insulating film to solve the problem of high melt viscosity of a high-filling system, obtain a low melt viscosity, and facilitate fine line filling; the resin composition has strong anti-corrosion ability, low surface roughness after Desmear treatment, high chemical copper bonding force, and low dielectric loss, and is suitable for making a high-filling system FC-BGA lamination film.
[0009] In the thermosetting resin composition of the present invention, the amount of the epoxy resin can be 30 parts by weight, 35 parts by weight, 38 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, or 70 parts by weight.
[0010] In the thermosetting resin composition of the present invention, the amount of the modified spherical silica powder can be 5 parts by weight, 10 parts by weight, 50 parts by weight, 100 parts by weight, 150 parts by weight, 200 parts by weight, 250 parts by weight, 300 parts by weight, 350 parts by weight, 400 parts by weight, 450 parts by weight, or 500 parts by weight.
[0011] In the thermosetting resin composition of the present invention, the amount of the curing agent can be 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, or 70 parts by weight.
[0012] In the present invention, the modified spherical silicon powder has a D50 particle size of 0.1 to 2.0 μm (e.g., 0.1 μm, 0.5 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, or 2.0 μm), and a particle size distribution coefficient of variation ≥ 35% (e.g., 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%, etc.), and the particle size distribution coefficient of variation can be adjusted to within the range of the specified particle size distribution coefficient of variation and the specified D50 particle size by grading the spherical silicon powder. When the particle size distribution coefficient of variation is within this range, the melt viscosity of the semi-cured insulating adhesive film produced is low, and the filling property and fluidity are good.
[0013] In the present invention, if the D50 particle size of the modified spherical silica powder is less than 0.1 μm, the melt viscosity of the semi-cured insulating film produced will increase significantly and the fluidity will deteriorate; if the D50 particle size of the modified spherical silica powder is greater than 2.0 μm, the ability to fill fine lines will weaken. If the coefficient of variation of the particle size distribution is less than 35%, the melt viscosity of the semi-cured insulating film produced will increase. The coefficient of variation, also known as the "standard deviation rate", is a statistic that measures the degree of variation of the particle sizes of each particle in the standard substance. The coefficient of variation of the particle size distribution of the standard substance is used to indicate the degree of dispersion of the particle size of the standard substance, and is usually expressed as a percentage of the standard deviation or the ratio of the standard deviation to the average particle size of the standard substance, the latter also known as dispersion. The calculation formula is: coefficient of variation = standard deviation / average particle size, the standard deviation needs to be further calculated through the statistical data of the Malvern particle size distribution, and the average particle size can be substituted using D50. The particle size involved in the present invention is tested by laser diffraction method, and the testing instrument is Malvern laser particle size analyzer, model MS3000.
[0014] Preferably, the amino-modified spherical silica powder comprises spherical silica powder modified with an aminosilane coupling agent, and the amount of the aminosilane coupling agent is 0.1-2% by weight of the spherical silica powder, for example 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.3%, 1.5%, 1.8% or 2%.
[0015] Preferably, the amino-modified spherical silicon micropowder is prepared by pre-treating the spherical silicon micropowder with a silazane compound and then modifying it with an aminosilane coupling agent. Pre-treating the spherical silicon micropowder with a silazane compound can completely remove the OH group (bound water) on the surface of the filler, improve the consistency of the surface treatment effect of the aminosilane coupling agent, make the spherical silicon micropowder as an inorganic substance and the resin compound as an organic substance more uniformly and fully integrated, and help reduce the dielectric loss of the insulating film.
[0016] Preferably, the silazane compound is selected from any one or a combination of at least two of hexamethyldisilazane, 1,3-divinyl-1,1,3,3-tetramethyldisilazane, octamethyltrisilazane, hexa(tert-butyl)disilazane, hexabutyldisilazane, hexaoctyldisilazane, 1,3-diethyltetramethyldisilazane, 1,3-di-n-octyltetramethyldisilazane, 1,3-diphenyltetramethyldisilazane, 1,3-dimethyltetraphenyldisilazane, 1,3-diethyltetramethyldisilazane, 1,1,3,3-tetraphenyl-1,3-dimethyldisilazane, 1,3-dipropyltetramethyldisilazane, hexamethylcyclotrisilazane, hexaphenyldisilazane, dimethylaminotrimethylsilazane, trisilazane, cyclotrisilazane or 1,1,3,3,5,5-hexamethylcyclotrisilazane.
[0017] Preferably, the amount of carbon per unit surface area of the amino-modified spherical silicon powder is 0.20 mg / m 2 -0.50mg / m 2 , for example 0.20 mg / m 2 , 0.30mg / m 2 , 0.35mg / m 2 , 0.4mg / m 2 , 0.45mg / m 2 or 0.50 mg / m 2 Too much carbon content will reduce the lamination stability, reliability and environmental resistance of the film, while too little carbon content will reduce the bonding strength between the inorganic spherical silica powder and the organic resin compound, and the resin will not play the role of filling.
[0018] In the present invention, the degree of surface treatment performed by a surface treatment agent can be evaluated by the amount of carbon per unit surface area. The amount of carbon per unit surface area of the amino-modified spherical silica powder can be measured in the following manner: the surface-treated amino-modified spherical silica powder is cleaned with methyl ethyl ketone and then measured. Specifically, 30 g of methyl ethyl ketone can be added to 15 g of amino-modified spherical silica powder that has been surface-treated with a surface treatment agent, ultrasonically cleaned at 25°C for 5 minutes, the supernatant is removed, and the solid component is dried. The carbon amount per unit surface area of 0.3 g of amino-modified spherical silica powder taken symmetrically is measured using a carbon analyzer. The carbon analyzer can use EMIA-320V of Horiba, Ltd.
[0019] Preferably, the aminosilane coupling agent is selected from any one of N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, aminopropylmethoxysilane or aminopropyltriethoxysilane, or a combination of at least two thereof.
[0020] Preferably, the epoxy resin is selected from any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, linear phenolic epoxy resin, dicyclopentadiene phenolic epoxy resin, biphenyl phenolic epoxy resin, aralkyl phenolic epoxy resin, aralkyl biphenyl phenolic epoxy resin, aralkyl naphthol phenolic epoxy resin or naphthalene epoxy resin.
[0021] Preferably, the curing agent is selected from any one of an amine curing agent, a cyanate resin, an active ester, a phenolic resin or an anhydride curing agent, or a combination of at least two thereof.
[0022] Preferably, the thermosetting resin composition further comprises a carbodiimide resin.
[0023] Preferably, the carbodiimide resin is any one of carbodiimide resins containing an aliphatic structure or an aromatic structure, or a combination of both.
[0024] Preferably, based on 100 parts by weight of the total weight of component (A), component (C) and component (D), the amount of the carbodiimide resin is 1-10 parts, for example, 1 part, 3 parts, 5 parts, 7 parts, 9 parts or 10 parts.
[0025] Preferably, the thermosetting resin composition further comprises other fillers (E);
[0026] Preferably, the other fillers include inorganic fillers and / or organic fillers.
[0027] Preferably, the inorganic filler is selected from any one or a combination of at least two of crystalline silica, fused silica, spherical silica, hollow silica, glass powder, aluminum nitride, boron nitride, silicon carbide, aluminum hydroxide, titanium dioxide, strontium titanate, barium titanate, aluminum oxide, barium sulfate, talc, calcium silicate, calcium carbonate or mica.
[0028] Preferably, the organic filler is selected from any one of polytetrafluoroethylene powder, polyphenylene sulfide, polyetherimide, polyphenylene ether or polyether sulfone powder, or a combination of at least two thereof.
[0029] Preferably, based on the total weight of component (A), component (C) and component (D) as 100 parts by weight, the total addition amount of the modified spherical silica powder (B) and other fillers (E) is 5 to 500 parts, for example, 5 parts by weight, 10 parts by weight, 30 parts by weight, 50 parts by weight, 80 parts by weight, 100 parts by weight, 150 parts by weight, 200 parts by weight, 250 parts by weight, 300 parts by weight, 350 parts by weight, 400 parts by weight, 450 parts by weight or 500 parts by weight.
[0030] In the present invention, under the premise of not affecting the comprehensive performance of the thermosetting resin composition, a thermoplastic resin may be further added, and the thermoplastic resin may be, for example, a polyimide resin, a phenolic resin, a polyphenylene ether, an acrylate resin, a polyvinyl acetal resin, a polyamide-imide resin, a polyethersulfone resin, a polysulfone resin or a core-shell rubber.
[0031] Preferably, the thermosetting composition further comprises a curing accelerator (F).
[0032] Preferably, the curing accelerator is selected from any one or a combination of at least two of an organic metal salt compound, an imidazole compound and its derivatives, a piperidine compound or a tertiary amine.
[0033] Preferably, the curing accelerator is selected from any one of 2-methylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, tri-n-butylamine, triphenylphosphine, boron trifluoride complex, metal octanoate, metal acetylacetonate, metal cyclohexane, metal salicylate or metal stearate, or a mixture of at least two thereof, wherein the metal is selected from any one of zinc, copper, iron, tin, cobalt or aluminum, or a combination of at least two thereof.
[0034] Preferably, based on the total weight of component (A), component (C) and component (D) as 100 parts by weight, the amount of the curing accelerator (F) is 0.01 to 1 part, for example, 0.01 part by weight, 0.03 part by weight, 0.05 part by weight, 0.08 part by weight, 0.1 part by weight, 0.3 part by weight, 0.5 part by weight, 0.8 part by weight or 1 part by weight.
[0035] In another aspect, the present invention provides a resin adhesive solution, wherein the resin adhesive solution comprises the thermosetting composition as described above and a solvent.
[0036] Preferably, the solvent is selected from any one of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene or xylene, or a combination of at least two thereof.
[0037] In another aspect, the present invention provides an insulating adhesive film, wherein the insulating adhesive film comprises the thermosetting composition as described above.
[0038] In the present invention, the preparation method of the insulating adhesive film comprises the following steps: mixing a thermosetting composition and a solvent to obtain a resin adhesive solution, coating the resin adhesive solution on a substrate, baking, removing the substrate, and obtaining the insulating adhesive film.
[0039] Preferably, the substrate is any one of a PET release film, a polyethylene film, a polypropylene film or a polyvinyl chloride film.
[0040] Preferably, the thickness of the substrate is 10 to 150 μm, for example, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm, more preferably 20 to 60 μm.
[0041] Preferably, the baking temperature is 80-120°C; for example, 80°C, 90°C, 100°C, 110°C or 120°C.
[0042] Preferably, the baking time is 1 to 10 min, for example, 1 min, 3 min, 5 min, 8 min or 10 min.
[0043] Preferably, the thickness of the insulating adhesive film is 10-100 μm, for example, 10 μm, 30 μm, 50 μm, 80 μm or 100 μm.
[0044] Preferably, the melt viscosity of the insulating adhesive film is 500-2100 Pa·s, for example, 500 Pa·s, 600 Pa·s, 700 Pa·s, 800 Pa·s, 900 Pa·s, 1000 Pa·s, 1200 Pa·s, 1500 Pa·s, 1800 Pa·s, 2000 Pa·s or 2100 Pa·s.
[0045] Preferably, after curing, the dielectric loss of the insulating adhesive film is ≤0.0182, for example, 0.0112, 0.0129, 0.0131, 0.0133, 0.0134, 0.0136, 0.0166, 0.0176 or 0.0182.
[0046] Preferably, the surface roughness Ra value of the insulating film after Desmear treatment is ≤0.360μm (for example, 0.36μm, 0.35μm, 0.32μm, 0.31μm, 0.29μm, 0.28μm, 0.27μm, 0.25μm or 0.22μm), and the chemical copper bonding force is ≥5.7N / cm (for example, 5.70N / cm, 6.10N / cm, 6.40N / cm, 6.50N / cm, 6.60N / cm, 7.10N / cm, 7.90N / cm or 8.10N / cm).
[0047] The insulating adhesive film of the present invention uses a semi-additive method or an additive method to prepare circuits and is applied in FC-BGA (Flip Chip Ball Grid Array, a packaging format of a flip chip ball grid array). The insulating adhesive film has both low surface roughness and high chemical copper bonding after etching, solving the technical problem of having both low surface roughness and high copper foil peeling strength that has long plagued the field.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] In the present invention, by using modified spherical silica powder in an epoxy system and controlling the range of its D50 particle size and the coefficient of variation of particle size distribution, the resin composition can be used for an insulating film to solve the problem of high melt viscosity of a high-filling system, obtain a low melt viscosity, and facilitate fine line filling; the resin composition has strong anti-corrosion ability, low surface roughness after Desmear treatment, high chemical copper bonding force, and low dielectric loss, and is suitable for making a high-filling system FC-BGA lamination film. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0051] The information of the modified spherical silicon powder used in the examples and comparative examples is as follows:
[0052] Modified spherical silicon powder 1: 100 parts by weight of spherical silicon powder was placed in a mixer, and the spherical silicon powder was stirred while spraying a vaporized aminosilane coupling agent (0.2 parts by weight, 3-aminopropyltrimethoxysilane, KBM-903, Shin-Etsu Chemical) and reacted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of modified spherical silicon powder 1 was 0.5 μm, and the coefficient of variation of particle size distribution was 50%.
[0053] Modified spherical silicon powder 2: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized aminosilane coupling agent (0.4 parts by weight, N-phenyl 3-aminopropyltrimethoxysilane, KBM-573, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder. The reaction lasted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of modified spherical silicon powder 2 was 0.5 μm, and the coefficient of variation of particle size distribution was 50%.
[0054] Modified spherical silicon powder 3: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized silazane compound (0.2 parts by weight, hexamethyldisilazane, SZ-31, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder, and the reaction was continued for 10 minutes to obtain spherical silicon powder pretreated with silazane; then, a vaporized aminosilane coupling agent (0.4 parts, N-phenyl 3-aminopropyltrimethoxysilane, KBM-573, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder, and the reaction was continued for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of modified spherical silicon powder 3 was 0.5 μm, and the coefficient of variation of particle size distribution was 50%.
[0055] Modified spherical silicon powder 4: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized aminosilane coupling agent (0.4 parts by weight, N-phenyl 3-aminopropyltrimethoxysilane, KBM-573, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder. The reaction lasted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of modified spherical silicon powder 4 was 0.7 μm, and the coefficient of variation of particle size distribution was 50%.
[0056] Modified spherical silicon powder 5: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized aminosilane coupling agent (0.4 parts by weight, N-phenyl 3-aminopropyltrimethoxysilane, KBM-573, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder. The reaction lasted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of modified spherical silicon powder 5 was 1.0 μm, and the coefficient of variation of particle size distribution was 50%.
[0057] Modified spherical silicon powder 6: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized aminosilane coupling agent (0.4 parts by weight, N-phenyl 3-aminopropyltrimethoxysilane, KBM-573, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder. The reaction lasted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of the modified spherical silicon powder 6 was 0.5 μm, and the coefficient of variation of the particle size distribution was 40%.
[0058] Modified spherical silicon powder 7: 100 parts by weight of spherical silicon powder was placed in a mixer, and the spherical silicon powder was stirred while spraying a vaporized aminosilane coupling agent (0.4 parts by weight, N-phenyl 3-aminopropyltrimethoxysilane, KBM-573, Shin-Etsu Chemical) and reacted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of modified spherical silicon powder 7 was 0.5 μm, and the coefficient of variation of particle size distribution was 60%.
[0059] Modified spherical silicon powder 8: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized aminosilane coupling agent (0.4 parts by weight, ethylene trimethoxysilane, KBM-1003, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder. The reaction lasted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of the modified spherical silicon powder 8 was 0.5 μm, and the coefficient of variation of the particle size distribution was 40%.
[0060] Modified spherical silicon powder 9: 100 parts by weight of spherical silicon powder was placed in a mixer, and the spherical silicon powder was stirred while spraying a vaporized aminosilane coupling agent (0.4 parts by weight, 3-glycidyloxypropyltrimethoxysilane, KBM-403, Shin-Etsu Chemical) and reacted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of the modified spherical silicon powder 9 was 0.5 μm, and the coefficient of variation of the particle size distribution was 40%.
[0061] Modified spherical silicon powder 10: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized aminosilane coupling agent (0.4 parts by weight, 3-methacryloxypropyltrimethoxysilane, KBM-503, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder. The reaction lasted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of the modified spherical silicon powder 10 was 0.5 μm, and the coefficient of variation of the particle size distribution was 40%.
[0062] Modified spherical silicon powder 11: 100 parts by weight of spherical silicon powder was placed in a mixer, and a vaporized aminosilane coupling agent (0.4 parts by weight, N-phenyl 3-aminopropyltrimethoxysilane, KBM-573, Shin-Etsu Chemical) was sprayed while stirring the spherical silicon powder. The reaction lasted for 10 minutes to obtain amino-modified pretreated spherical silicon powder. The D50 of the modified spherical silicon powder 11 was 0.5 μm, and the coefficient of variation of the particle size distribution was 20%.
[0063] Example 1
[0064] 45 parts by weight of epoxy resin (NC-3000-H, Nippon Kayaku), 50 parts by weight of phenolic resin (MEH-7851H, Meiwa Chemical), 100 parts by weight of modified spherical silica powder 1, 5 parts by weight of carbodiimide resin (HMV-10B, Nisshinbo), 10 parts by weight of other fillers (spherical silica, SC-2050MB, Admatechs) and 0.1 parts by weight of curing accelerator (2E4MZ) were added to butanone solvent and stirred for 2 hours to form a resin glue with a solid content of 65%. The resin glue was coated on a PET release film and baked in a 120°C oven for 5 minutes to obtain an insulating adhesive film.
[0065] The compositions of the thermosetting resin compositions of Examples 2-12 and Comparative Examples 1-4 are shown in Tables 1-3, wherein the amounts of the components are in parts by weight.
[0066] Table 1
[0067]
[0068] Table 2
[0069]
[0070]
[0071] Table 3
[0072]
[0073]
[0074] The obtained insulating film was subjected to a performance test, and the test method was as follows:
[0075] <Minimum melt viscosity>
[0076] Take 350 mg of semi-cured insulating film as a sample, grind it into powder, and use an oscillating rheometer to measure it. The heating rate is 3°C / min and the test temperature is 40-180°C. The horizontal axis of the test curve is temperature, and the vertical axis is melt viscosity. The lowest melt viscosity point is taken to read the value in Pa·s.
[0077] <Dielectric loss tangent value (D f )>
[0078] Take a fully cured insulating film sample with a length of 80 mm, a width of 80 mm, and a thickness of 40 μm, fix the sample on an Agilent impedance material analyzer using an Agilent 16453A measuring fixture, perform a test scan, and determine the dielectric loss tangent value at 1 GHz.
[0079] <Arithmetic mean of roughness profile (Ra)>
[0080] The insulating film was pressed onto the surface of the core board and cured in an oven at 180°C for 30 minutes to obtain a pre-cured insulating film. The insulating film was subjected to the following Desmear treatment: soaked in an aqueous solution of glycol ether and sodium hydroxide (MV Sweller, ATOTECH) at 70°C for 10 minutes - washed with deionized water for 2 minutes - soaked in a potassium permanganate solution (MV P-Etch, ATOTECH) at 80°C for 30 minutes - washed with deionized water for 2 minutes - soaked in an acidic aqueous solution (MV Reduction Cleaner, ATOTECH) at 50°C for 5 minutes to obtain a roughened insulating film, and the surface Ra after the roughening treatment was tested using a laser confocal instrument (OLYMPUS).
[0081] <Chemical copper bonding strength (PS)>
[0082] The roughened insulating film was subjected to the following copper deposition, electroplating and post-curing treatments: soaked in chemical copper solution (MVTP1, ATOTECH) for 20 minutes - electroplated copper with a thickness of 25 μm - cured in an oven at 200°C for 60 minutes, and the copper foil peel strength tester was used to test the copper bonding strength of the insulating film.
[0083] As can be seen from Tables 1 to 3, the minimum melt viscosity of the insulating adhesive film of Examples 1 to 12 of the present application is 500-2100 Pa·s, the surface roughness Ra value after Desmear treatment is 0.22-0.36 μm, the chemical copper bonding force is 5.7-8.1 N / cm, and the dielectric loss is 0.0112-0.0182. Compared with Example 5, the modified spherical silicon powder of Example 6 is pre-treated with a silazane compound, and the OH group (bound water) on the surface of the filler is completely removed, which improves the consistency of the surface treatment effect of the coupling agent, and the insulating adhesive film obtains a lower dielectric loss.
[0084] In Comparative Examples 1-3, spherical silicon powder modified by vinyl, epoxy or methacrylic silane coupling agents were used respectively, and the minimum melt viscosity of the insulating film obtained was average, and the surface roughness Ra value increased significantly after Desmear treatment, but it was not conducive to improving the chemical copper bonding strength, and the electroplated copper penetrated too deeply into the insulating film, which had a hidden danger in the long-term interlayer insulation reliability. The coefficient of variation of the particle size distribution of the modified spherical silicon powder used in Comparative Example 4 was only 20%, and the minimum melt viscosity of the insulating film obtained was too high, which was not conducive to the filling of fine circuits.
[0085] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the thermosetting resin composition and the insulating adhesive film of the present invention, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A thermosetting resin composition, characterized in that The thermosetting resin composition comprises the following components in parts by weight: 30-70 parts of epoxy resin (A), 5-500 parts of modified spherical silica powder (B) and 30-70 parts of curing agent (C), wherein the modified spherical silica powder is amino-modified spherical silica powder, the D50 particle size of the modified spherical silica powder is 0.1-2.0 μm, and the coefficient of variation of particle size distribution is ≥35%; The amino-modified spherical silicon micropowder is prepared by pre-treating the spherical silicon micropowder with a silazane compound and then modifying it with an aminosilane coupling agent.
2. The thermosetting resin composition according to claim 1, characterized in that The amount of the aminosilane coupling agent is 0.1-2% of the weight of the spherical silicon powder.
3. The thermosetting resin composition according to claim 1, characterized in that The silazane compound is selected from any one or a combination of at least two of hexamethyldisilazane, 1,3-divinyl-1,1,3,3-tetramethyldisilazane, octamethyltrisilazane, hexa(tert-butyl)disilazane, hexabutyldisilazane, hexaoctyldisilazane, 1,3-diethyltetramethyldisilazane, 1,3-di-n-octyltetramethyldisilazane, 1,3-diphenyltetramethyldisilazane, 1,3-dimethyltetraphenyldisilazane, 1,3-diethyltetramethyldisilazane, 1,1,3,3-tetraphenyl-1,3-dimethyldisilazane, 1,3-dipropyltetramethyldisilazane, hexamethylcyclotrisilazane, hexaphenyldisilazane, dimethylaminotrimethylsilazane, trisilazane or cyclotrisilazane.
4. The thermosetting resin composition according to claim 1, characterized in that The aminosilane coupling agent is selected from any one of N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane or aminopropyltriethoxysilane, or a combination of at least two thereof.
5. The thermosetting resin composition according to claim 1, characterized in that: The epoxy resin is selected from any one of bisphenol A epoxy resin, bisphenol F epoxy resin, linear phenolic epoxy resin, dicyclopentadiene phenolic epoxy resin, biphenyl phenolic epoxy resin, aralkyl phenolic epoxy resin, aralkyl biphenyl phenolic epoxy resin, aralkyl naphthol phenolic epoxy resin or naphthalene epoxy resin, or a combination of at least two thereof.
6. The thermosetting resin composition according to claim 1, characterized in that: The curing agent is selected from any one of amine curing agents, cyanate resins, active esters, phenolic resins or anhydride curing agents, or a combination of at least two of them.
7. The thermosetting resin composition according to claim 1, characterized in that: The thermosetting resin composition further includes a carbodiimide resin (D).
8. The thermosetting resin composition according to claim 7, characterized in that: The carbodiimide resin is any one of carbodiimide resins containing an aliphatic structure or an aromatic structure, or a combination of both.
9. The thermosetting resin composition according to claim 7, characterized in that: Based on 100 parts by weight of the total weight of component (A), component (C) and component (D), the amount of the carbodiimide resin is 1 to 10 parts.
10. The thermosetting resin composition according to claim 1, characterized in that: The thermosetting resin composition further includes other fillers (E).
11. The thermosetting resin composition according to claim 10, characterized in that: The other fillers include inorganic fillers and / or organic fillers.
12. The thermosetting resin composition according to claim 11, characterized in that: The inorganic filler is selected from any one or a combination of at least two of crystalline silica, fused silica, spherical silica, hollow silica, glass powder, aluminum nitride, boron nitride, silicon carbide, aluminum hydroxide, titanium dioxide, strontium titanate, barium titanate, aluminum oxide, barium sulfate, talc, calcium silicate, calcium carbonate or mica.
13. The thermosetting resin composition according to claim 11, characterized in that: The organic filler is selected from any one of polytetrafluoroethylene powder, polyphenylene sulfide, polyetherimide, polyphenylene ether or polyether sulfone powder, or a combination of at least two thereof.
14. The thermosetting resin composition according to claim 10, characterized in that: Based on 100 parts by weight of the total weight of component (A), component (C) and component (D), the total addition amount of the modified spherical silica powder (B) and other fillers (E) is 5 to 500 parts.
15. The thermosetting resin composition according to claim 1, characterized in that: The thermosetting resin composition further includes a curing accelerator (F).
16. The thermosetting resin composition according to claim 15, characterized in that: The curing accelerator is selected from any one of an organic metal salt compound, an imidazole compound and its derivatives, a piperidine compound or a tertiary amine, or a combination of at least two thereof.
17. The thermosetting resin composition according to claim 15, characterized in that: The curing accelerator is selected from any one of 2-methylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, tri-n-butylamine, triphenylphosphine, boron trifluoride complex, metal octanoate, metal acetylacetonate, metal cyclohexane, metal salicylate or metal stearate, or a mixture of at least two of them, wherein the metal is selected from any one of zinc, copper, iron, tin, cobalt or aluminum, or a combination of at least two of them.
18. The thermosetting resin composition according to claim 15, characterized in that: Based on 100 parts by weight of the total weight of component (A), component (C) and component (D), the amount of the curing accelerator (F) is 0.01 to 1 part.
19. A resin glue, characterized in that: The resin glue comprises the thermosetting resin composition as described in any one of claims 1 to 18 and a solvent.
20. The resin glue according to claim 19, characterized in that: The solvent is selected from any one of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene or xylene, or a combination of at least two thereof.
21. An insulating film, characterized in that: The insulating adhesive film comprises the thermosetting resin composition according to any one of claims 1 to 18.
22. The insulating adhesive film according to claim 21, characterized in that: The thickness of the insulating film is 10-100 μm.
23. The insulating adhesive film according to claim 21, characterized in that: The melting viscosity of the insulating adhesive film is 500-2100 Pa·s.
24. The insulating adhesive film according to claim 21, characterized in that: The dielectric loss of the insulating adhesive film after curing is ≤0.0182.
25. The insulating adhesive film according to claim 21, characterized in that: The insulating film has a surface roughness Ra value of ≤0.360 μm and a chemical copper bonding strength of ≥5.7 N / cm after Desmear treatment.
Citation Information
Patent Citations
Insulating resin composition for multilayer printed wiring board, insulating resin sheet with base material, multilayer printed wiring board, and semiconductor device
CN101772526A